(untitled) (Prima Journal of Integrated Studies, 2026)
In progress blood of the flow main biomechanical features , including viscosity , Poiseuille Reynolds ’s law turbulence criteria and vein of the wall elasticity in detail seeing Blood is released . of the flow disorders with related cardiological pathologies and their prevent to take methods analysis will be done.